Handgrip difference between young karate athletes and non-athles in relation to gender - Vukovic, V.; Koropanovski, N. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
Handgrip is positively established marker for evaluation of body strength in general. Even though several recent studies in combat sports have highlighted the role of handgrip force (HGF) in sports achievement, the impact of training, in particular in karate, on development of the HGF parameters in children before puberty has not been sufficiently explored. Having regard to these issues, the present study aimed to reveal existence of contractile differences in male and female preadolescents i.e. karate athletes and non-athletes in relation to activity. A total of 219 children (Male n = 125, karate athletes = 73, non-athletes = 52; Female n = 94, karate athletes = 48, non-athletes = 46), age from 10 to 13 years, participated in the study. Both hands, dominant and non-dominant, were tested using the standard handgrip test and the highest value from two trials was used to determine the maximal isometric handgrip force (Fmax) and the maximal rate of force development (RFD). Multivariate analysis of variance (MANOVA) revealed the existence of differences between karate athletes vs. nonathletes in male subjects (F=5.07; p<0.000; .2=0.27), as well as in female subjects (F=4.84; p<0.000; .2=0.33) at general level. The results are indicating that there are no statistically significant differences between male karate athletes and non-athletes regarding Fmax, but higher values of RFD are evidenced in favor to non-athletes in both absolute and relative terms. Girls training karate achieve statistically higher values of Fmax, but only in right hand both absolute and relative terms, while there are no differences when it comes to the left one. When it comes to RFD, evidence favors non-athletes in absolute terms. The results are most probably indicating that differences in RFD regarding boys and girls occurs as a consequence of a non-adequate intermuscular coordination caused by basic karate training. On the contrary to that, positive effect of training is evident in girls, but only when it comes to maximal force